1979
DOI: 10.7164/antibiotics.32.446
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation of the antibiotic ristomycin A. The amino acid constituents.

Abstract: Hydrolysis of the O-methylated aglycone of ristomycin A by a mixture of KOH and NaBH4 yielded a mixture of aromatic amino acids which, after N-acetylation and Ome.hylation, were separated by chromatography on silica gel. Compounds III' VII were isolated and identified by pmr and mass spectroscopy.Compounds V -VII were also oxiiatively degraded to the corresponding benzoate esters. Compounds III and IV are derived from ristomycinic acid (I) and V from actinoidinic acid (II), both of which had been obtained in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Several recent structural studies of glycopeptide antibiotics1~5) have shown that these antibiotics appear to hold several chemical features in common. Typically, glycopeptides give rise to an "aglycone," neutral sugars"') and an amino sugar upon mild hydrolysis', [1][2][3][4][5][6][7][8][9][10][11][12]. Furthermore, the aglycone is a complex peptide which retains the same amino acids present in the parent after total hydrolysis and also some of the antimicrobial activity of the parent.…”
Section: Bacteriamentioning
confidence: 99%
“…Several recent structural studies of glycopeptide antibiotics1~5) have shown that these antibiotics appear to hold several chemical features in common. Typically, glycopeptides give rise to an "aglycone," neutral sugars"') and an amino sugar upon mild hydrolysis', [1][2][3][4][5][6][7][8][9][10][11][12]. Furthermore, the aglycone is a complex peptide which retains the same amino acids present in the parent after total hydrolysis and also some of the antimicrobial activity of the parent.…”
Section: Bacteriamentioning
confidence: 99%
“…The fact that the magnitudes of the chemical shift perturbations induced by Pr(III) increase with increasing metal ion concentration indicates that the antibiotic is in fast exchange on the NMR chemical shift time scale between its free and complexed states. The chemical shift perturbations in the presence of paramagnetic ions can be expressed as -Act 4" ^+ (7) where Act is the complex formation shift and is diamagnetic in origin, Ac is the shift arising from the Fermi contact interaction, and Ad is the shift arising from the dipolar interaction. In the present system Act is negligible since the spectrum of Blenoxane is unaffected by the presence of a saturating concentration of (28) (a) J. Reuben, "Handbook on the Physics and Chemistry of the Rare Earths", Vol.…”
Section: *N-[n][b]/[nb]mentioning
confidence: 99%